2017
DOI: 10.1089/wound.2016.0725
|View full text |Cite
|
Sign up to set email alerts
|

Topical Naltrexone Is a Safe and Effective Alternative to Standard Treatment of Diabetic Wounds

Abstract: Objective: Diabetes affects more than 29 million individuals in the United States, resulting in healthcare costs approaching $245 billion. Approximately 15% of these individuals will develop a chronic, non-healing foot ulcer (diabetic foot ulcer [DFU]) that, if untreated, may lead to amputation. The current treatments for DFU are expensive, have significant side-effects, and often result in non-compliance. A new topical treatment is described that accelerates cutaneous wound repair and is disease modifying by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Omega-3 fatty acids significantly decreased the diabetic wound area by affecting the concentration of MCs [97]. Topical administration of 0.03% naltrexone, an opioid receptor antagonist, could accelerate diabetic wound closure by promoting deoxyribonucleic acid synthesis, increasing MCs, and enhancing the expression of PDGF and VEGF [98]. DSCG in subcutaneously mesh-implanted C57BL/6J mice decreased early inflammation and fibrotic responses [99].…”
Section: Mcs Stabilizersmentioning
confidence: 97%
“…Omega-3 fatty acids significantly decreased the diabetic wound area by affecting the concentration of MCs [97]. Topical administration of 0.03% naltrexone, an opioid receptor antagonist, could accelerate diabetic wound closure by promoting deoxyribonucleic acid synthesis, increasing MCs, and enhancing the expression of PDGF and VEGF [98]. DSCG in subcutaneously mesh-implanted C57BL/6J mice decreased early inflammation and fibrotic responses [99].…”
Section: Mcs Stabilizersmentioning
confidence: 97%
“…In numerous clinical trials, rhPDGF-BB has been shown to help in the treatment of chronic lower extremity diabetic ulcers by increasing the incidence of complete healing as well as functioning as a safe therapy that is well tolerated (Steed and Study Group, 1995 ; Smiell et al, 1999 ). Naltrexone (NTX) is an alternative therapy that is FDA approved for systemic application and is currently being evaluated for topical treatment (McLaughlin et al, 2017 ). Internationally, Trafermin (AdisInsight, 2016 ) and Nepidermin (AdisInsight, 2015 ) are also used for the treatment of decubitus wounds but are not FDA approved for clinical use in the US.…”
Section: Wound Dressingsmentioning
confidence: 99%
“…Whether this was due to activation of mast cells or due to depletion of mast cell granules is unknown, as pre-operative injection resulted in quicker closure of perforations than post-operative injection. In a diabetic rat model, treatment with naltrexone, an opioid receptor antagonist, was as effective as the standard of care for improving wound healing [152]. Notably, naltrexone increased both the amounts of mast cells at the healing site and the amount of angiogenesis [152,153].…”
Section: Wound Healing and Angiogenesismentioning
confidence: 99%
“…In a diabetic rat model, treatment with naltrexone, an opioid receptor antagonist, was as effective as the standard of care for improving wound healing [152]. Notably, naltrexone increased both the amounts of mast cells at the healing site and the amount of angiogenesis [152,153]. While it is not known whether naltrexone effects mast cells directly, it is likely that an increase in their numbers would improve healing in diabetic wounds which typically display lower amount of mast cells than non-diabetic models [152].…”
Section: Wound Healing and Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation